Varstrometry for Dual Active Galactic Nuclei Using Radio Interferometry: VaDAR with the VLBA - Emma Schwartzman; Paula Fudolig; Tracy E. Clarke; Kristina Nyland; Nathan J. Secrest; Ryan W. Pfeifle; Henrique Schmitt; Shobita Satyapal; Barry Rothberg (The Astrophysical Journal, 2025)
Multiple active galactic nuclei (multi-AGN) are a known result of galaxy mergers. Therefore, they are an important tool for studying the formation and dynamical evolution of galaxies and supermassive black holes. A novel method for the selection of multi-AGN leverages the exquisite positional accuracy of Gaia to detect astrometrically variable quasars. Previous work has paired this method with radio interferometry on subarcsecond scales. In this paper, we present a follow-up study of seven astrometrically variable quasars from the pilot sample using the Very Long Baseline Array (VLBA). We targeted these seven quasars with the VLBA at 2.0–2.4 GHz ( S band) and 8.0–8.4 GHz ( X band), reaching milliarcsecond resolutions, in order to study the radio properties at smaller scales and to constrain the origin of the astrometric variability. The new observations are also used to identify significant radio-optical offsets in all seven objects, suggesting that many astrometrically variable quasars also exhibit significant radio-optical offsets. We find that four of the seven sources are possible candidate multi-AGN based on their radio properties and radio-optical offsets. Overall, we use this follow-up study to constrain the smaller-scale radio properties of this sample of astrometrically variable quasars, and continue to explore the use of this method in the field of multi-AGN.